Effects of reinforcement during the intertrial interval on temporal discrimination: Location version with rats - Pérez-Calzada, Mario; Zamora-Arevalo, Oscar (Frontiers in Behavioral Neuroscience, 2022)
Different studies on temporal control of behavior have focused on making modifications to experimental tasks by introducing disruptors to know how these manipulations modify temporal control. The aim of this study was to produce changes on temporal discrimination in a temporal bisection task with a disruptor associated with motivation, which consisted in delivering reinforcement during the intertrial interval (RITI). Four Wistar rats and a pair of duration 2s-8s were used. There were two types of sessions: baseline generalization, where the disruptor was not applied and RITI generalization, where disruptive manipulation was applied. The analysis of results consisted of comparing psychophysical parameters, Signal Detection Theory indices, and latencies to start trials of baseline sessions and disruption sessions. The results showed a change on point of subjective equality, a change on psychophysical function and an increasing trend in the latencies to start trials on RITI disruption and no change on Signal Detection Theory indices. The results highlight the importance of incorporating motivational explanations to theories on temporal control in non-human organisms.